2013
DOI: 10.1136/bcr-2013-010011
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of haemodialysis to treat phenobarbital overdose

Abstract: SUMMARYA 50-year-old woman presented with coma caused by a phenobarbital overdose, requiring intubation and admission to critical care. She was an international visitor and had been prescribed the drug for nightsedation. Phenobarbital is a long-acting barbiturate, which in an overdose can cause central nervous system depression, respiratory failure and haemodynamic instability; these patients can remain obtunded for many days. After initial supportive therapy, she was dialysed to help in the elimination of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Applications of hemodialysis and hemoperfusion in phenobarbital intoxications have been reported in the literature. Hoyland et al reported that they used hemodialysis in 2 sessions of 2.5 hours in a patient who had phenobarbital intoxication (9). In their study, it was reported that blood phenobarbital levels were reduced from 115 mcg/mL to 84 mcg/ mL in the first session and from 78 mcg/mL to 55 mcg/ mL (approximately 30%) in the second session.…”
Section: Discussionmentioning
confidence: 90%
“…Applications of hemodialysis and hemoperfusion in phenobarbital intoxications have been reported in the literature. Hoyland et al reported that they used hemodialysis in 2 sessions of 2.5 hours in a patient who had phenobarbital intoxication (9). In their study, it was reported that blood phenobarbital levels were reduced from 115 mcg/mL to 84 mcg/ mL in the first session and from 78 mcg/mL to 55 mcg/ mL (approximately 30%) in the second session.…”
Section: Discussionmentioning
confidence: 90%
“…A few studies have been done to correlate early hemodialysis with decreased morbidity and early recovery. [ 3 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Two previous case reports showed similar favorable results in phenobarbital overdosage treated by hemodialysis with a blood-flow rate between 180 ml/min and 200 ml/min and dialysate-flow rate of 500 ml/min. [ 11 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…There have been multiple case reports regarding successful extracorporeal treatment in severe barbiturate intoxication. 3,4,6,[9][10][11][12][13][14] Haemodialysis involves solute removal by diffusion whereas haemofiltration uses convection with hydrostatic pressure inducing plasma water filtration across the haemofilter. 6 Haemoperfusion is ideal in the removal of lipid soluble or highly protein bound drugs.…”
Section: Discussionmentioning
confidence: 99%
“…2 Prescription rates have also declined with the development of safer antiepileptics like levetiracetam and anxiolytics like benzodiazepine. 3 Despite these two factors, acute barbiturate poisoning is still common due to its affordability in developing countries and ongoing prescription in human/animal epilepsy disorders such as partial and tonicclonic generalized seizures. 4 Clinicians need to recognise the symptoms and physiology of barbiturate overdose.…”
Section: Introductionmentioning
confidence: 99%